TRANSITION FROM WEB FORMS TO .NET MVC - EXPERIENCE IN INTERNET TECHNOLOGY COURSE - Kostoska, Magdalena; Koteska, Bojana; Armenski, Goce (IATED, 2020)
This paper presents our experience with technology transition in Internet technology course at our University. It reports on a case study aimed at developing a better curriculum and improving student experience with the course. It outlines the motivation for the changes and the challenges. The goal of the paper is to examine the students' perceived quality of learning and the students opinion regarding introduction of new more complex technology, in comparison to using older, but less complex technology. We use a survey methodology. The obtained result show students' satisfaction with the technology transition and willingness to invest more time in learning new technologies, despite increasing the difficulty level of the course and the volume of learning materials. The study in this paper draws upon the experiences of student participating in Internet Technologies course in the spring semester 2018 at the Ss. Cyril and Methodius University. It examines the students' perceived quality of learning and using a survey methodology, we attempt to detect the factors impacting students’ perceptions of course effectiveness and technology integration. We also relay our experience from the previous years (starting form 2014/2015) and our motivation for change of the material. Internet Technologies course is an elective course offered in the summer semester at Ss. Cyril and Methodius University, Faculty of Computer Science and Engineering. We use various learning methods in this course. In the lectures we use presentations, but in 2018 we also enriched them by introducing practical examples which were usually interactive. During exercises a real-life usage is demonstrated and in 2018 we created video tutorials, given the increased difficulty of the material. Our goal was to enable the students to replicate the examples by using the tutorial. We also introduced usage of GitHub repository in order to share the examples and projects. We invite guest lecturers to promote their experience with the technology. We also encourage teamwork and motivate the students to create real practical projects. The distribution of hours in each activity is the following: theoretical teaching (30 hours) and exercises (laboratory, auditory), seminar papers and teamwork (45 hours). Other activity forms include project tasks (15 hours), independent learning tasks (15 hours) and home learning (75 hours). The results of the survey show that the course was satisfactory, despite the increased complexity and the increased volume of the materials and topics. The results also show that we enabled the students to obtain knowledge in the subject, while raising interest. As a result the students suggested that they will further recommend the course to other colleagues. An interesting observation is that, while much larger portion of the students find the new technology material (.NET MVC) difficult, unlike the older technology (WebForms), in the same time they find the new technology much more useful. This observation shows that students are wiling to invest more time in learning to be competitive in todays' job market.
Keywords: MVC; .NET; Internet technology; University course